Survival and success of the relatively oldest in swiss youth skiing competition - Romann, R.; Fuchslocher, J. (International Journal of Sports Science and Coaching, 2014)
Relative age refers to age differences between children in the same selection year. The present study investigated the prevalence of relative age effects (RAEs) at the Grand Prix Migros (GPM), which is the most popular alpine skiing race for children aged 7 to 14 years in Europe. In total, 17,992 Swiss junior alpine skiers, separated into female skiers (n = 7,227) and male skiers (n = 10,765), were evaluated in the 2010, 2011, and 2012 races. Chi-square analyses revealed no RAEs (p > 0.05) for the entire group of finishers in the qualification race for females in the Under U-8 to U-13 categories (n = 7,010) and all males (n = 10,410). Significant inverse RAEs were detected in the qualification race among female skiers in the U-14 and U-15 age categories (p < 0.01; odds ratio OR = 0.79; 95% confidence interval (CI) [0.64-0.98], and among disqualified male skiers (p < 0.01; OR = 0.54; [CI, 0.40-0.74]. However, significant RAEs were found for the entire group of both female and male skiers who qualified for the final race (p < 0.01; OR = 1.49; [CI, 1.28-1.73] of females, respectively OR = 2.18; [CI, 1.87-2.53] of males). RAEs were additionally apparent in all age categories of female and male finalists. The GPM is apparently influenced by RAEs, which may be an initial step towards RAEs in youth sports and may lead to an unequal participation in Swiss skiing.